Method for preparing adhesive by recycling polyformaldehyde plastic
By mixing polyformaldehyde, biomass-derived glycol and catalyst for chemical degradation, cyclic acetal products are obtained and polymerized with cyclic anhydride to generate high value-added adhesives, which solves environmental pollution and waste residue treatment during the recycling of polyformaldehyde plastics The problem has achieved efficient and economical green recycling effect.
Patent Information
- Application Number
- CN202411567523.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-05
AI Technical Summary
The prior art has environmental pollution, safety hazards and waste residue treatment problems in the recycling process of polyformaldehyde plastics, and the treatment of degradation products is difficult to deal with, and lacks efficient and economical recycling methods.
By mixing polyformaldehyde, biomass-derived glycol and catalyst, heating and stirring, salting and dehydration, cyclic acetal product is obtained, and ring-opening polymerization with cyclic anhydride to form a high value-added adhesive.
It realizes green recycling of polyformaldehyde plastics, generates high value-added adhesives, reduces process costs, and is simple to operate, with the advantages of green economy and sustainable development.
Smart Images

Figure CN119431757A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of chemical materials, and in particular to a method for recycling polyoxymethylene plastic to prepare an adhesive. Background Art
[0002] Polyoxymethylene (POM), also known as acetal resin, polyoxymethylene, and polyacetal, is a thermoplastic polymer with high heat resistance, bending strength, fatigue resistance, excellent wear resistance and electrical properties. It is known as "super steel" or "sport steel". However, during use, polyoxymethylene will experience natural aging phenomena such as cracking, deformation, and powdering, thereby generating a large amount of waste polyoxymethylene. In addition to slow natural weathering, conventional polyoxymethylene degradation methods mainly include chemical recycling and mechanical physical recycling. Chemical recycling is mainly chemical decomposition and depolymerization: for example, thermal depolymerization or polycondensation reaction of polyoxymethylene is performed to decompose it into small molecules or oligomers, which are used as new chemical raw materials. For example, the degradation method using strong acid as a catalyst, but the use of strong acid will cause pollution to the environment, and the inevitable volatilization during use will also cause harm to the human body and equipment, and the generated waste residue is also difficult to handle.
[0003] Chinese patent CN106397325A discloses an imidazole ionic liquid and its application in the degradation of polyoxymethylene, which relates to the technical field of ionic liquids and provides a means of saving the amount of acid catalyst for the degradation of polyoxymethylene plastics; the preparation method of the ionic liquid comprises the following steps: 1) preparation of [ATMIM]Cl3 (1,2,3-tri(N-methylimidazolyl)-1-propylene trichloride); 2) taking [ATMIM]Cl3, dissolving it in water, purging it with inert gas, heating it to room temperature -80°C, adding a raw material containing a target anion, the raw material molar ratio of [ATMIM]Cl3 to the target anion is 1:(3-4), stirring and blowing the reaction until no HCl is detected, stopping the reaction, purifying, and obtaining an ionic liquid. The process conditions for preparing the ionic liquid of the invention are a two-step synthesis method, and the degradation product is formaldehyde, which needs to be collected at -30°C, and the subsequent treatment is difficult. Therefore, providing an efficient and economical degradation method for polyoxymethylene plastics is a problem that needs to be solved in the prior art. Summary of the invention
[0004] The purpose of the present invention is to provide a method for recycling polyformaldehyde plastics to prepare adhesives. The method provided by the present invention can recycle discarded polyformaldehyde plastics and convert them into high value-added products, thereby realizing green recycling of polyformaldehyde plastics, which is economical and environmentally friendly.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for recovering polyoxymethylene to prepare an adhesive, comprising the following steps:
[0007] (1) mixing polyoxymethylene, a biomass-derived diol, and a first catalyst to obtain a mixture;
[0008] (2) heating and stirring the mixture obtained in step (1) under sealed conditions, collecting fractions and cooling to obtain a liquid product;
[0009] The liquid phase product is sequentially subjected to salting out and dehydration to obtain a cyclic acetal product;
[0010] (3) mixing the cyclic anhydride, the solvent and the second catalyst to obtain a premix;
[0011] In an inert atmosphere, the cyclic acetal product obtained in step (2) is added dropwise to the premix to carry out a polymerization reaction to obtain an adhesive.
[0012] Preferably, the molecular weight of the polyoxymethylene in step (1) is 20,000 to 110,000.
[0013] Preferably, the biomass-derived diol in step (1) is one of ethylene glycol, 1,2-propylene glycol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, 1,2-pentanediol, 1,3-pentanediol, 1,4-pentanediol, 2,4-pentanediol, 1,2-hexanediol or 1,3-hexanediol.
[0014] Preferably, in the step (1), the mass ratio of the biomass-derived diol to the polyoxymethylene is (1-9):1.
[0015] Preferably, the first catalyst in step (1) is at least one of hydrochloric acid, sulfuric acid, trifluoromethanesulfonic acid, SnCl4·5H2O, SnCl4, SnCl2·2H2O, FeCl3·6H2O, ZnCl2 or AlCl3.
[0016] Preferably, the molar amount of the first catalyst in step (1) accounts for 0.2% to 7% of the molar amount of polyoxymethylene.
[0017] Preferably, the temperature of heating and stirring in step (1) is 100 to 140° C., and the time of heating and stirring is 1 to 6 hours.
[0018] Preferably, the cyclic anhydride in step (2) is at least one of glutaric anhydride, phthalic anhydride, itaconic anhydride, maleic anhydride and 1,2-cyclohexanedicarboxylic anhydride.
[0019] Preferably, the second catalyst in step (2) is at least one of trifluoromethanesulfonic acid or methyl trifluoromethanesulfonate.
[0020] Preferably, the polymerization reaction temperature in step (2) is 20 to 50° C., and the polymerization reaction time is 0.5 to 6 hours.
[0021] The invention provides a method for recovering polyformaldehyde to prepare an adhesive. Simple biomass-derived diol and petroleum-based polyformaldehyde plastic are heated and stirred under catalytic conditions to undergo dehydration condensation (chemical degradation) to generate a cyclic acetal product. A fraction containing the cyclic acetal product and water vapor is collected and cooled to obtain a liquid phase product. After salting out and dehydration treatment, a cyclic acetal product is obtained. The cyclic acetal product is then subjected to a ring-opening polymerization reaction with a cyclic acid anhydride under catalytic conditions to generate an adhesive. The method provided by the invention has low reaction cost and a product with high added value. The depolymerized fraction can be refined to obtain high-quality 1,3-dioxolane, i.e., a cyclic acetal product, which can be used as an organic solvent such as lignin, a chromatography solvent, a metal surface treatment agent, or the preparation of a pharmaceutical intermediate and a monomer. The polymerized product, i.e., an adhesive, can be used for bonding non-polar surfaces such as wood and PET boards, thereby realizing green, efficient and low-cost recovery of polyformaldehyde and having high practical application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The cyclic acetal product obtained in Example 1 of the present invention 1 H-NMR spectrum;
[0023] Figure 2 The adhesive prepared in Example 1 of the present invention 1 H-NMR spectrum. DETAILED DESCRIPTION
[0024] The present invention provides a method for recovering polyoxymethylene to prepare an adhesive, comprising the following steps:
[0025] (1) mixing polyoxymethylene, a biomass-derived diol, and a first catalyst to obtain a mixture;
[0026] (2) heating and stirring the mixture obtained in step (1) under sealed conditions, collecting fractions and cooling to obtain a liquid product;
[0027] The liquid phase product is sequentially subjected to salting out and dehydration to obtain a cyclic acetal product;
[0028] (3) mixing the cyclic anhydride, the solvent and the second catalyst to obtain a premix;
[0029] In an inert atmosphere, the cyclic acetal product obtained in step (2) is added dropwise to the premix to carry out a polymerization reaction to obtain an adhesive.
[0030] In the present invention, unless otherwise specified, the raw materials used are conventional commercial products in the art.
[0031] The present invention mixes polyoxymethylene, biomass-derived diol and a first catalyst to obtain a mixture.
[0032] In the present invention, the molecular weight of the polyoxymethylene is preferably 20000 to 110000. In the present invention, the polyoxymethylene is preferably waste polyoxymethylene plastic.
[0033] In the present invention, the biomass-derived diol is preferably one of ethylene glycol, 1,2-propylene glycol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, 1,2-pentanediol, 1,3-pentanediol, 1,4-pentanediol, 2,4-pentanediol, 1,2-hexanediol or 1,3-hexanediol. In the present invention, the mass ratio of the biomass-derived diol to the polyoxymethylene is (1-9):1, more preferably (1-8):1. The molar ratio of the biomass-derived diol to the polyoxymethylene is controlled within the above range to prevent the product 1,3-dioxolane from decomposing in an acidic environment due to excessive concentration of the product.
[0034] In the present invention, the first catalyst is preferably at least one of hydrochloric acid, sulfuric acid, trifluoromethanesulfonic acid, SnCl4·5H2O, SnCl4, SnCl2·2H2O, FeCl3·6H2O, ZnCl2 or AlCl3. In the present invention, the molar amount of the first catalyst is preferably 0.2% to 7% of the molar amount of polyoxymethylene, more preferably 0.5% to 5%. The present invention controls the amount of the first catalyst within the above range to ensure that the polyoxymethylene plastic can be effectively degraded.
[0035] After obtaining the mixture, the present invention heats and stirs the mixture under a sealed condition, collects fractions and cools the fractions to obtain a liquid product.
[0036] In the present invention, the temperature of the heating and stirring is preferably 100-140°C; the time of the heating and stirring is preferably 1-6 hours, more preferably 2-4 hours. The present invention controls the temperature and time of the heating and stirring within the above range to ensure efficient degradation of polyoxymethylene plastic. The present invention has no specific restrictions on the speed of the heating and stirring, and a speed well known in the art can be used to achieve uniform stirring.
[0037] In the present invention, the heating and stirring process is preferably accompanied by ultrasonic treatment; the power of the ultrasonic treatment is preferably 200-300 W, more preferably 250 W. The present invention uses ultrasonic treatment as a condition for external field strengthening, which can reduce the amount of catalyst, shorten the reaction time and lower the reaction temperature, thereby improving the reaction efficiency.
[0038] The present invention has no particular limitation on the cooling method, and the condensation to obtain the liquid product can be achieved by using the technical solutions well known in the art.
[0039] After the fractions are collected in the present invention, the residual liquid in the reactor is preferably continued for the next circulation reaction.
[0040] After obtaining the liquid phase product, the present invention sequentially performs salting out and dehydration on the liquid phase product to obtain a cyclic acetal product.
[0041] In the present invention, the dehydrating agent used for the salting out is preferably at least one of anhydrous calcium chloride, anhydrous sodium sulfate, anhydrous magnesium sulfate and anhydrous sodium chloride.
[0042] In the present invention, the molecular sieve used for dehydration is preferably at least one of type 3A molecular sieve, type 4A molecular sieve, type 5A molecular sieve, and 13XAPG molecular sieve.
[0043] The present invention mixes the cyclic anhydride, the solvent and the second catalyst to obtain a premix;
[0044] In the present invention, the cyclic anhydride is preferably at least one of glutaric anhydride, phthalic anhydride, itaconic anhydride, maleic anhydride, and 1,2-cyclohexanedicarboxylic anhydride. In the present invention, the molar ratio of the cyclic anhydride to the cyclic acetal product is preferably (0.5-3.5):1, more preferably (1-2.5):1. The present invention controls the molar ratio of the cyclic anhydride to the cyclic acetal product within the above range to ensure that the polymer product has a higher degree of alternation and a larger molecular weight.
[0045] In the present invention, the solvent is preferably at least one of dichloromethane, acetone, toluene and ethyl acetate.
[0046] In the present invention, the second catalyst is preferably at least one of trifluoromethanesulfonic acid or methyl trifluoromethanesulfonate.
[0047] After obtaining the cyclic acetal product and the premix, the present invention drips the cyclic acetal product into the premix in an inert atmosphere to carry out a polymerization reaction to obtain an adhesive.
[0048] In the present invention, the inert atmosphere is preferably a nitrogen atmosphere.
[0049] In the present invention, the polymerization reaction temperature is preferably 20 to 50°C, more preferably room temperature. In the present invention, the polymerization reaction time is preferably 0.5 to 6 hours, more preferably 2 to 4 hours. The present invention controls the polymerization reaction temperature and time within the above range to ensure that the polymerization monomer is polymerized to the maximum extent.
[0050] The method provided by the present invention is suitable for chemical degradation and recovery of waste polyoxymethylene plastics. A simple biomass-derived diol can be used for dehydration condensation with the diol under catalytic conditions to generate a cyclic acetal product, and the cyclic acetal product is converted into an adhesive that can be applied to a non-polar surface, thereby realizing the functional reuse of waste plastics. The process operation is simple, and the requirements for reaction equipment and experimental conditions are low. The method and process can realize the recycling of homogeneous catalysts, and has the advantages of green economic sustainability.
[0051] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0052] Example 1
[0053] A method for recovering polyoxymethylene to prepare an adhesive, comprising the following steps:
[0054] (1) 18.62 g of ethylene glycol, 3 g of polyoxymethylene having a molecular weight of 20,000 to 110,000, and 1.05 g of SnCl4·5H2O are placed in a reactor and mixed uniformly to obtain a mixture;
[0055] The mass ratio of the biomass-derived diol to the polyoxymethylene is 6.2:1; the molar amount of the first catalyst SnCl4·5H2O accounts for 3% of the molar amount of the polyoxymethylene;
[0056] (2) Under sealed conditions, the mixture obtained in step (1) is heated and stirred to 130° C. for reaction for 3 h, and the fractions are collected and naturally cooled to obtain a liquid product, and the residual liquid in the reactor is continued for the next cycle reaction;
[0057] The liquid product is salted out with CaCl2, and dehydrated with 4A molecular sieve to obtain a cyclic acetal product;
[0058] (3) 4.436 g of 1,2-cyclohexanedicarboxylic anhydride, 0.06 g of methyl trifluoromethanesulfonate and 2 ml of CH2Cl2 were mixed to obtain a premix;
[0059] In a nitrogen atmosphere, 1 mL of the cyclic acetal product obtained in step (2) was added dropwise to the premix and mixed evenly. The mixture was reacted at room temperature for 3 h, and then dried in a vacuum oven to remove the solvent to obtain an adhesive.
[0060] The molar ratio of the cyclic anhydride 1,2-cyclohexanedicarboxylic anhydride to the cyclic acetal product is 2:1.
[0061] The cyclic acetal product obtained in Example 1 of the present invention was detected by nuclear magnetic resonance. 1 H-NMR spectrum Figure 1 As shown. Figure 1 It can be determined that the cyclic acetal product prepared in Example 1 is 1,3-dioxolane.
[0062] The adhesive prepared in Example 1 of the present invention was detected by nuclear magnetic resonance. 1 H-NMR spectrum Figure 2 As shown. Figure 2 It can be determined that Example 1 of the present invention successfully synthesized an adhesive with a target structure.
[0063] Embodiments 2 to 10
[0064] Adhesives were prepared according to the method of Example 1. The difference from Example 1 is that the types and amounts of the first catalysts used in Examples 2 to 10 are shown in Table 1 below.
[0065] In order to study the effect of the type and amount of the first catalyst on the chemical degradation of polyoxymethylene in the method provided by the present invention, the conversion rate of polyoxymethylene (i.e., POM) in Examples 2 to 10 was calculated by weighing the remaining unreacted polyoxymethylene mass, and the yield of 1,3-dioxolane in step (2) described in Examples 2 to 10 was detected by gas chromatography. The detection results are shown in Table 1, wherein in Table 1, when the first catalyst is HCl, 37% hydrochloric acid is added to the mixture until the pH value is 3.45; "catalyst amount / mol%" represents the molar percentage of the first catalyst in POM.
[0066] Table 1 Effects of different first catalyst types and dosages on chemical degradation of polyoxymethylene
[0067]
[0068]
[0069] As shown in Table 1, SnCl4·5H2O is the best catalyst, and the yield of the product of the chemical degradation of polyoxymethylene plastic can reach 74%.
[0070] According to the method of Example 1, the residual liquid in the reactor of Example 1 is continued to be subjected to the next cycle reaction to carry out the polyoxymethylene plastic chemical degradation cycle process, and the cycle is repeated 6 times. The conversion rate of polyoxymethylene (i.e., POM) and the yield of 1,3-dioxolane in each cycle are respectively detected according to the above-mentioned detection method. The concentration of 1,3-dioxolane in the fraction is detected by gas chromatography. The stability parameters of the polyoxymethylene plastic chemical degradation cycle process using the method of Example 1 of the present invention are shown in Table 2 below.
[0071] Table 2 Stability parameters of polyoxymethylene plastic chemical degradation cycle process
[0072]
[0073]
[0074] It can be seen from Table 2 that after 6 cycles, the conversion rate of polyoxymethylene plastic has not decreased, which proves the feasibility of the cycle, and the total 1,3-dioxolane yield is 85.35%.
[0075] Embodiments 12 to 15
[0076] An adhesive was prepared according to the method of Example 1, except that the molar ratios of the cyclic anhydride 1,2-cyclohexanedicarboxylic anhydride and the cyclic acetal product in Examples 12 to 15 were 1:1, 1.5:1, 2:1, and 2.5:1, respectively.
[0077] The adhesives prepared in Examples 12 to 15 were used to bond a single-layer 3 mm thick wood board and a PET board, with one layer of each board bonded. The amount of adhesive used was 0.2 g / cm 2 The shear strength of the bonded PET board was tested using an M221C testing machine. The performance test data are shown in Table 3 below.
[0078] Table 3 Adhesive performance parameters of polymer products
[0079]
[0080] In summary, due to the presence of ether bonds, polyoxymethylene plastics can be converted into high-value-added degradation products such as cyclic acetals through chemical degradation, among which water and a very small amount of trioxymethylene are by-products.
[0081] Therefore, the final purification can be carried out by distillation and subsequent refining to obtain high-quality cyclic acetal products; or after dehydration treatment, it can be used together with cyclic anhydride as a raw material for adhesives to synthesize adhesives that can be applied to non-polar surfaces, with excellent bonding properties and degradability.
[0082] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for recovering polyoxymethylene to prepare an adhesive, characterized in that: The following steps are involved: (1) mixing polyoxymethylene, a biomass-derived diol, and a first catalyst to obtain a mixture; (2) heating and stirring the mixture obtained in step (1) under sealed conditions, collecting fractions and cooling to obtain a liquid product; The liquid phase product is sequentially subjected to salting out and dehydration to obtain a cyclic acetal product; (3) mixing the cyclic anhydride, the solvent and the second catalyst to obtain a premix; In an inert atmosphere, the cyclic acetal product obtained in step (2) is added dropwise to the premix to carry out a polymerization reaction to obtain an adhesive.
2. The method according to claim 1, characterized in that: The molecular weight of the polyoxymethylene in the step (1) is 20,000 to 110,000.
3. The method according to claim 1, characterized in that The biomass-derived diol in step (1) is one of ethylene glycol, 1,2-propylene glycol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, 1,2-pentanediol, 1,3-pentanediol, 1,4-pentanediol, 2,4-pentanediol, 1,2-hexanediol or 1,3-hexanediol.
4. The method according to claim 1 or 3, characterized in that: In the step (1), the mass ratio of the biomass-derived diol to the polyoxymethylene is (1-9):
1.
5. The method according to claim 1, characterized in that The first catalyst in step (1) is at least one of hydrochloric acid, sulfuric acid, trifluoromethanesulfonic acid, SnCl4·5H2O, SnCl4, SnCl2·2H2O, FeCl3·6H2O, ZnCl2 or AlCl3.
6. The method according to claim 1 or 5, characterized in that: The molar amount of the first catalyst in the step (1) accounts for 0.2% to 7% of the molar amount of the polyoxymethylene.
7. The method according to claim 1, characterized in that The heating and stirring temperature in step (1) is 100 to 140° C., and the heating and stirring time is 1 to 6 hours.
8. The method according to claim 1, characterized in that In the step (2), the cyclic anhydride is at least one of glutaric anhydride, phthalic anhydride, itaconic anhydride, maleic anhydride and 1,2-cyclohexanedicarboxylic anhydride.
9. The method according to claim 1, characterized in that: The second catalyst in step (2) is at least one of trifluoromethanesulfonic acid or methyl trifluoromethanesulfonate.
10. The method according to claim 1, characterized in that The polymerization reaction temperature in step (2) is 20 to 50° C., and the polymerization reaction time is 0.5 to 6 hours.
Citation Information
Patent Citations
Imidazole-type ionic liquid and application thereof to degradation of polyformaldehyde
CN106397325A
Preparation method of benzaldehyde glycerol acetal
CN112174927A
Biomass alcoholysis method for petroleum-based plastic POM
CN112724118A
Process for producing polyoxymethylene-polyalkylene oxide block copolymers
CN113195575A
Green, safe and environment-friendly process for industrial continuous large-scale production of formaldehyde-free water-based adhesive
CN113801611A